A nucleation-tuned mechanism to prepare centre-crossed zeolite lamellas by the rotating/static switch crystallization strategy. Issue 5 (25th January 2022) - Wang, Jing; Zhang, Xinlan; Chen, Lihua; Lu, Xinhuan; Xia, Qinghua; Zhou, Dan
Abstract : Controllable synthesis of zeolite lamellas with different morphology and property by tuning the nucleation process. Abstract : Although it is normally considered that hydrothermal synthesis is difficult to be controlled, the controllable synthesis of zeolite and related materials is believed to be possible by tuning the crystal nucleation process based on the study in this work. Herein, a switch crystallization strategy (SCS) is developed to prepare zeolite lamellas by the combination of crystallizations under rotating and static hydrothermal conditions. Particularly, by the initial crystallization under relatively high rotation rate conditions for 12 hours and the consequent static crystallization for 10 days (R + S route), MWW zeolite lamellas with a unique centre-crossed morphology and hierarchically porous structure can be directly synthesized (centre-crossed zeolite lamellas, CCZL). Through systematic studies of crystallization conditions and processes, it is found that the rotation rate of the autoclave has an important influence on the particle size and morphology of the zeolite precursor prepared by 'R + S' route, and the formation of CCZL is ascribed to the vital roles of external forces aroused by rotation in the electrostatic and van der Waals interactions among various reaction species in the gel mixture during the nucleation stage. Moreover, the CCZL materials show efficient catalytic performance in the acid-catalysis condensation reaction of ethylene glycol with benzaldehyde or cyclohexanone, which is ascribed to their excellent physical and chemical properties, including a large BET surface area, suitable acid property, highly exposed and accessible catalytic sites over the centre-crossed MWW zeolite lamellas, and so on.